Implementasi Metode Simple Additive Weighting Pada Aplikasi Penentukan Karyawan Terbaik - Wowon Priatna; Joniwarta Joniwarta; Rinaldi Tunnisia (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Election of the best employees is an important aspect of employee performance management in a company because it produces useful information for employee administrative decisions such as promotions, awards, and other decisions. Making the best employee selection not only selects and determines the right employees, but it is also important for managers to plan mature policies in motivating and developing potential employees. The problem with choosing the best employees in company agencies is the difficult decision making by managers in determining who the best employees are really worthy because of limited time and the number of employees and work that must be done by managers so that the best employee implementation is only chosen by the manager and assessment. The criteria are ignored which causes the assessment results to be subjective. One of the methods built to solve problems in the best employee decision making is done by using the Simple Additive Weighting (SAW) method, which is then ranked for the best alternative in the form of employee assessment scores. In this study, the implementation of SAW used 5 criteria to determine the best employees, namely skills, personality, initiative, attendance and loyalty. The calculation results from the implementation of the SAW method are used as a reference for designing the best employee determination application. The system design uses the Unified Modeling Language (UML) and builds applications with PHP programming and MySQL databases.